Warum der Hase lange Ohren hat - Auer, Martin 1951-; Wolfsgruber, Linda 1961- (Gabriel-Verl., 1999)
When will the little rabbit have long ears like his papa? What makes the little rabbit's ears grow?
Keywords: Jungtiere; Strafe; Erziehung; Feldhase; Bilderbuch